PENGEMBANGAN MODUL MATEMATIKA BERBASIS RME UNTUK SISWA KELAS 1 SEKOLAH DASAR - Ira Mira; Rachmiati, Wida; Wahyu Wibowo, Eko (Jurnal keilmuan dan Kependidikan dasar, 2023)
Based on observations, there are low mathematics scores for measurement material in 2 different schools. This happened due to the COVID 19 factor and lack of parental guidance. Therefore, as a reference, researchers developed RME-based mathematics teaching materials in the form of realistic mathematics education-based modules. This research uses the R&D method. aims to determine the procedures, feasibility and effectiveness of the module. Based on the research carried out, the results of the research are: procedures carried out based on the ADDIE model, validation from media and material experts respectively 75% and 76%. And this product is considered effective because it can liven up the classroom atmosphere and get student and teacher questionnaire scores of 100% and 85% respectively.